Human granulocytes undergo cell death via autophagy. Issue 1 (December 2018) - Kajiume, Teruyuki; Kobayashi, Masao
Abstract Mature neutrophils must be quickly removed from inflammatory sites to prevent tissue damage. Neutrophil removal is thought to be accomplished primarily through caspase-dependent apoptosis, which involves several genes of mitochondrial origin. However, mature neutrophils show reduced gene transcription and mitochondrial numbers. We predicted that neutrophils utilize other cell death mechanisms and investigated programmed cell death in human peripheral blood mononuclear cells (MNCs) and polymorphonuclear cells (PMNCs or neutrophil fractions). Unlike MNCs, PMNCs did not undergo DNA fragmentation and were not TUNEL positive, but expressed LC3-II, an autophagy marker. We also found that during differentiation, autophagy inhibitor 3-MA, and not caspase inhibitor zVAD-fmk, prevented segmentation of the nucleus, indicating that these cells undergo autophagy during maturation. Therefore, human neutrophils may undergo spontaneous autophagic cell death rather than apoptosis, during which autophagy may be essential for both maturation and death.